The Influence of Digital Marketing on Gold Investment Product Purchase Decisions at PT Pegadaian Sumedang Branch - Munawar, Anwar; Gumilang, Risa Ratna; Nur'arif, Muhammad Irfan (Journal of Bussines Management Basic, 2025)
Digital transformation and technological advancements have altered how businesses engage with their customers. Consumer behavior and purchasing patterns have changed as a result of the internet and mobile devices becoming an essential part of daily life. Digital marketing has become a crucial tactic for businesses looking to stay competitive in a market that is becoming more and more dynamic. The purpose of this study was to ascertain how digital marketing affected the choices made by PT Pegadaian Sumedang Branch customers about gold investment products. A quantitative descriptive method is used in this investigation. The research sample consisted of 80 individuals employing accidental sampling procedures, whereas the research population consisted of 100 PT Pegadaian Sumedang Branch customers. Questionnaires, interviews, and observation were the methods utilized to gather data. Validity and reliability tests were part of this study's correlation test. Simple linear regression analysis was the method of data analysis employed. The findings demonstrated that digital marketing had a favorable and noteworthy impact on PT Pegadaian Sumedang Branch customers' decisions to buy gold investment goods. It can be concluded that digital marketing has a significant impact on purchasing decisions because the determinant's coefficient value in this study was 0.653, or 65.3%. However, other factors not covered in this study have an impact on the remaining 34.7%.